Uji Efikasi Ekstrak Batang Tembakau (Nicotiana spp.) untuk Pengendalian Rayap Tanah (Coptotermes spp.) - Arbaiatusholeha, Rizki; Yuliawati, Sri; Saraswati, Lintang Dian (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Coptotermes spp. is one of the most harmful termites, because it can damage the wood and building. One of the controlling efforts is by using a tobacco stalk extract, due to the nicotine and other bioactive compounds and are toxic to the termite. This study aims to know the effectiveness of the tobacco stalk extract for termite control. This research is experimental study. The study is conducting for 21 days. Sample for each treatment is 150 termites, where each treatment is 0% (control), 1.3%; 2%; 3.4%; 6.8%; 9.7% with 5 repetitions. It is obtaining from pre-test. Termite mortality data, weight modification of feed paper, and termite consumption are analyzing with ANOVA and followed by Tukey test at 1% significant results. Lethal Concentration (LC) 50 and 90 are analyzing with Probit regression. The results show that the value of termites mortality on test Tukey is p<0,01. And the values of weight modification of paper and termite consumption on test Tukey are p<0,01. So there is significant difference on termite mortality. For weight modification of paper and termite consumption, there are significant differences. Unless the concentration of 1%; 2%; 3.4%; 6.8% and 9.7% are not significant. The values of Lethal Concentration (LC) 50 and 90 are 1,715% and 6.945%. The hope is the community can do termite control easily by utilizing the tobacco stalk.